2015
DOI: 10.11114/ijsss.v3i4.857
|View full text |Cite
|
Sign up to set email alerts
|

Agreeableness, Extraversion, Stressor and Physiological Stress Response

Abstract: Based on the theoretical analysis, with first-hand data collection and using multiple regression models, this study explored the relationship between agreeableness, extraversion, stressor and stress response and figured out interactive effect of agreeableness, extraversion, and stressor on stress response. We draw on the following conclusions: (1) the interaction term of stressor (work) and agreeableness can negatively predict physiological stress response; (2) the interaction term of stressor (health) and agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
9
0
4
Order By: Relevance
“…While some previous research supports a relationship between stress, neuroticism, and clinical depression ( Pereira-Morales, Adan, & Forero, 2019 ), our measure of Neuroticism—Depression represents a general tendency towards moodiness as opposed to a persistent and sometimes debilitating disorder. Amongst the other BFI domains, and in line with existing literature, we found that Conscientiousness and Agreeableness were negatively correlated with stress levels ( Bibbey et al, 2013 , Chu et al, 2015 , Martens et al, 2009 ). However, in contrast with previous studies that report high levels of Conscientiousness and Agreeableness are associated with lower overall alcohol use ( Malouff et al, 2007 , Roberts and Bogg, 2004 ), we found that these traits were not negatively associated with alcohol use/misuse when considering covariates and comorbid personality domains.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While some previous research supports a relationship between stress, neuroticism, and clinical depression ( Pereira-Morales, Adan, & Forero, 2019 ), our measure of Neuroticism—Depression represents a general tendency towards moodiness as opposed to a persistent and sometimes debilitating disorder. Amongst the other BFI domains, and in line with existing literature, we found that Conscientiousness and Agreeableness were negatively correlated with stress levels ( Bibbey et al, 2013 , Chu et al, 2015 , Martens et al, 2009 ). However, in contrast with previous studies that report high levels of Conscientiousness and Agreeableness are associated with lower overall alcohol use ( Malouff et al, 2007 , Roberts and Bogg, 2004 ), we found that these traits were not negatively associated with alcohol use/misuse when considering covariates and comorbid personality domains.…”
Section: Discussionsupporting
confidence: 90%
“…Personality factors have also been linked to stress levels, with previous studies identifying a strong positive correlation between stress and Neuroticism ( Gunthert et al, 1999 , Schneider, 2004 ). Contrastingly, studies have demonstrated negative correlations between Conscientiousness ( Martens et al, 2009 ) and Agreeableness ( Bibbey et al, 2013 , Chu et al, 2015 ) with stress. Neuroticism, as measured by the Big Five Inventory (BFI), describes an individual’s emotional instability and propensity to experience negative emotions ( John & Srivastava, 1999 ).…”
Section: Introductionmentioning
confidence: 80%
“…On other dimensions of the FFM, extraversion, in interaction with various types of stressors (health, family, social, work) can negatively predict physiological stress response [157]. Higher extraversion may be associated with a low level of sAA [40], lower levels of basal/or increased salivary testosterone [5], lower cortisol reactivity [154], and lower cardiovascular reactivity [153] to psychological stress.…”
Section: Introductionmentioning
confidence: 99%
“…Although in a study, agreeableness of FFM in interaction with various types of stressors (health, family, social, work) negatively predicted physiological stress response [157], but also, there are some dissimilar findings. For example, individuals with low levels on agreeableness tended to have higher levels of diastolic blood pressure, systolic blood pressure and urinary epinephrine [156], and on the other hand, these people also have shown lower levels of cortisol and cardiac reactions to stress [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, extroversion would negatively predict depression (Mohamadi Hasel, Besharat, Abdolhoseini, Alaei Nasab, & Niknam, 2013). According to two meta-analyses from 2015, agreeableness, extroversion (Chu, Ma, Li, & Han, 2015a), and openness to experience negatively predict the psychological answer to stress, whereas conscientiousness predicts it positively (Chu et al, 2015b).…”
Section: Is Perceived Stress Of French University Students Related To 44mentioning
confidence: 99%